Phylogenetic relationship and characterization of the complete mitochondrial genome of Cheilomenes sexmaculata (Coleoptera: Coccinellidae). Issue 8 (3rd August 2021) - Cheng, Gaoqi; Du, Yimin; Liu, Xinjun
Abstract: Cheilomenes sexmaculata is a common natural enemy for aphid and psyllid in agricultural systems in South China. In this study, we sequenced and analyzed the complete mitochondrial genome (mitogenome) of C. sexmaculata . This mitogenome was 17, 297 bp long and encoded 13 protein-coding genes (PCGs), 22 transfer RNA genes (tRNAs) and two ribosomal RNA unit genes (rRNAs). Gene order was conserved and identical to most other previously sequenced Coccinellidae. All PCGs of C. sexmaculata have the conventional start codon for invertebrate mitochondrial PCGs (ATN), with the exception of cox1 (AAT) and nad3 (TTG). Except for seven genes ( cox1, cox2, cox3, nad3, nad5, nad4 and nad6 ) end with the incomplete stop codon T−, all other PCGs terminated with the stop codon TAA or TAG. The whole mitogenome exhibited heavy AT nucleotide bias (78.0%). Phylogenetic analysis positioned C. sexmaculata in a well-supported clade with Aiolocaria hexaspilota . The relationships (Sticholotidinae + (Coccinellinae + (Scymninae + Epilachninae))) were supported in Coccinellidae, and Halyziini was paraphyletic to Coccinellini within Coccinellinae.